Determination of Biochemical Composition and Mineral Contents of Deep Sea Pink Shrimp (Parapenaeus longirostris Lucas, 1846) Caught from the Gulf of Izmit, Turkey - (:unkn) unknown (KAFKAS UNIV, VETERINER FAKULTESI DERGISI, 2010)
The aim of this study is to identify seasonal variation of biochemical composition and mineral content (K, Na, Ca, Fe, Mg) in abdominal muscle tissues and hepatopancreas of the Deep sea pink shrimp (Parapenaeus longirostris) caught from of the Gulf of Izmit, Turkey. Deep sea pink shrimps is an abundant penaeid species which inhabits the Gulf Izmit and they were collected seasonaly. In the laboratory, abdominal muscles and hepatopancreas were removed for determination of glycogen, free glucose, total lipid, triglyceride, total cholesterol levels and mineral content. Furthermore, K, Na, Ca, Fe, Mg levels have determined in abdominal muscle tissues of females and males. Our findings in Parapenaeus longirostris suggest that lipids and carbohydrates are main reserve of metabolic energy used during physiological activities in both males and female shrimps.
Keywords: Parapenaeus longirostris; Deep sea pink shrimp; Biochemical composition; Mineral content; Gulf of Izmit; CHEMICAL-COMPOSITION; SEASONAL-VARIATIONS; TIGER SHRIMP; HIGH-PROTEIN; CRAB; CRUSTACEANS; METABOLISM; METAL; CARBOHYDRATE; DECAPODA